(Un-)sustainable transformations: everyday food practices in Italy during COVID-19. Issue 1 (9th December 2022) - Forno, Francesca; Laamanen, Mikko; Wahlen, Stefan
Abstract: In this article, we study how the global pandemic has affected food practices. We underscore how time, space, and modality as key facets of the everyday intersect with understandings, procedures, and engagements as components of practice, and how food practices in the pandemic context are transforming, at least temporarily, toward more sustainability. Our mixed-methods data were collected from participants in a local food initiative established in Trento during the first Italian lockdown in Spring 2020, which aimed to connect local producers to consumers more directly. We analyze data from a panel survey conducted with 55 participants of this initiative followed by ten in-depth interviews six months after the lockdown. The findings illustrate that the lockdown encouraged different people to search for "good food" through the food initiative. Sustainable food practices included more planning and less waste, but in some cases initial interest in the initiative changed back to prevailing industrial supply via supermarkets. Thus, not all food practices of our respondents were transformed to be more sustainable or permanent. We conclude that everyday food practices, when disrupted and if accompanied with well-functioning socio-technical innovations, can foster a transformation toward a more diversified and sustainable food system.